Dopamine in Tourette syndrome: a 30-year bibliometric analysis of hotspot evolution - Liu, Qian; Zhu, Zhiyao; Luo, Fei; Ding, Yali; Wang, Yuanyuan; Zhao, Changjiang; Yuan, Bin (Frontiers in Neurology, 2025)
IntroductionTourette syndrome (TS), a neurodevelopmental disorder, requires attention to the physical and psychological impacts of tics and associated comorbidities. Researchers are making efforts to clarify the pathophysiology of TS and develop effective treatments amidst its rising global prevalence. This study aimed to retrieve publications discussing TS in the context of the dopaminergic system from 1994 to 2023, summarize previous research, and analyze the general information and hotspots to provide references for future research and clinical applications.MethodsLiterature was filtered from the Web of Science Core Collection. Excel, CiteSpace, VOSviewer, and Scimago Graphica were used to analyze and visualize the results.ResultsA total of 482 related publications were included in the study. The United States has consistently led in research output, and Yale University demonstrates excellence in workload, impact, and collaboration. Harvey S. Singer has the highest number of publications. The hotspots include comorbidities, dopaminergic Components, candidate genes, and deep brain stimulation.DiscussionThe analysis reveals that the understanding of TS is gradually evolving towards neuronal and genetic mechanisms. Concurrently, deep brain stimulation is being investigated as a treatment for refractory TS. These findings suggest a need for more in-depth research to produce higher-level evidence.